Alterations in p53 predict response to preoperative high dose chemotherapy in patients with gastric cancer. Issue 5 (26th September 2003) - Bataille, F; Rümmele, P; Dietmaier, W; Gaag, D; Klebl, F; Reichle, A; Wild, P; Hofstädter, F; Hartmann, A
Abstract : Aims: To evaluate the usefulness of molecular markers in predicting histopathological and clinical response to preoperative high dose chemotherapy (HDCT) and survival of patients with advanced gastric cancer. Methods: In a phase II trial, 25 patients with metastatic gastric cancer received preoperative tandem HDCT consisting of etoposide, cisplatin, and mitomycin, followed by autologous bone marrow transplantation to achieve surgical resectability. Samples before and after treatment, from normal and tumour tissue, were characterised histopathologically, and both p53 and BAX expression was analysed by immunohistochemistry. Pretreatment formalin fixed, paraffin wax embedded samples from normal and tumour tissue were microdissected, and the extracted DNA was preamplified using improved primer extension preamplification polymerase chain reaction. Detection of microsatellite instability (MSI) or loss of heterozygosity (LOH) was performed using markers for p53, BAX, BAT25, BAT26, D2S123, D17S250, and APC. Exons 5–9 of the p53 gene were sequenced directly on ABI 373. Results: Four parameters were significantly associated with response to chemotherapy and prolonged overall survival: positive p53 immunostaining, positive p53 mutation status before chemotherapy, strong histological regression induced by preoperative HDCT, and surgical treatment. Patients's sex or age, tumour location or stage, lymph node status, Lauren classification, MSI, or LOH did not influence duration of survival significantly in this high risk population. Conclusion: Positive p53 immunostaining and p53 mutation status in pretreatment tumour biopsies might be useful molecular predictors of response and prognosis in patients with advanced gastric cancer treated by preoperative HDCT.